Can Strategy and Innovation Drive Performance Through Competitive Advantage? - Fikrul Hakim; Ni Wayan Widya Ekarani; Cokorda Gede Govinda Partha; Anak Agung Diah Tarama Devi (Journal Of Business, Finance, and Economics (JBFE), 2025)
This paper attempts to is to understand and analyze the influence of business strategy and innovation capabilities on business performance in cafes in Semarang City, where competitive advantage serves as a mediator. The research population consisted of 221 cafes registered with the Semarang City Cafe Association (ASOKAS). The research was conducted using a census method, involving all members of the population. This study utilized Structural Equation Modeling (SEM) for data analysis, implemented through AMOS 26. The findings of this research reveal that competitive advantage contributes positively and significantly to business performance, business strategy reveals a significant positive effect on business performance, business strategy reveals a significant positive effect on competitive advantage, innovation capability significantly and positively affects business performance, and also significantly enhances competitive advantage. The conclusion of this study is that competitive advantage, business strategy, and a positive impact on café business performance in Semarang City.